Gastroesophageal Reflux and Asthma: Can the Paradox Be Explained? - Stephen K Field (Canadian Respiratory Journal)
BACKGROUND AND OBJECTIVE: The reported effects of asthma on gastroesophageal reflux (GER), effects of GER on asthma and the effects of antireflux therapy on asthma are conflicting. The purpose of this paper is to review the evidence for a relationship between the two conditions.